Solar Orbiter Data‐Model Comparison in Venus' Induced Magnetotail. Issue 2 (11th February 2023) - Stergiopoulou, Katerina; Jarvinen, Riku; Andrews, David J.; Edberg, Niklas J. T.; Dimmock, Andrew P.; Kallio, Esa; Persson, Moa; Khotyaintsev, Yuri V.
Abstract: We investigate the structure of the Venusian magnetotail utilizing magnetic field and electron density measurements that cover a wide range of distances from the planet, from the first two Solar Orbiter Venus flybys. We examine the magnetic field components along the spacecraft trajectory up to 80 Venus radii down the tail. Even though the magnetic field behavior differs considerably between the two cases, we see extended electron density enhancements covering distances greater than ∼20 R V in both flybys. We compare the magnetic field measurements with a global hybrid model of the induced magnetosphere and magnetotail of Venus, to examine to what degree the observations can be understood with the simulation. The model upstream conditions are stationary and the solution encloses a large volume of 83  R V  × 60  R V × 60 R V in which we look for spatial magnetic field and plasma variations. We rotate the simulation solution to describe different stationary upstream IMF clock angle cases with a 10° step and find the clock angle for which the agreement between observations and model is maximized along Solar Orbiter's trajectory in 1‐min steps. We find that in both flybys there is better agreement with the observations when we rotate the model for some intervals, while there are parts that cannot be well reproduced by the model irrespective of how we vary the IMF clock angle, suggesting the presence of non‐stationary features in  the Venus‐solar wind interaction not accounted for in the hybrid model. Key Points: We examine rare observations of the distant induced magnetotail of Venus made by Solar Orbiter during its first two flybys We compare Venus flyby data with a hybrid simulation and investigate the level of the data‐model agreement during different intervals We observe electron density enhancements at great distances from the planet and different magnetic field features between the two flybys